Embracing New (and Old) Ideas - James E. Daily (Washington University Journal of Law & Policy, 2017)
This Essay, by James E. Daily, lecturer at Washington University School of Law, identifies current declines in the demand for legal education and the greater job market offers a possible solution—re-introducing the LL.B degree. Daily looks at the historical increases in demand that led to the acceptance of the J.D. as the standard law degree required for practice. Daily proposes law schools should re-organize the current J.D. program to become a research or theory-focused advanced degree, and re-introduce the LL.B undergraduate LL.B degree that integrates the use and creation of new technologies in legal practice.
Keywords: Washington University School of Law; ABA; modern technology; legal education; LL.B; J.D.; law students; legal profession; job market; legal practice; research; advanced degree